Mathtype, Version 3.0. (1993) - Clay Clay, David W. David W.
Abstract : MathType is a mathematical equation editor in the Windows 3.1 environment. It lets you build up any kind of mathematical expression by using simple point-and-click techniques and then insert them into any Windows 3.1 compatible word processor; for instance, Word Perfect 5.1/5.2 for Windows, Word 2.0 for Windows, and AMI Pro 3.0 for Windows. An expression designed by MathType can be transferred into a word processor by using standard Cut and Paste commands or by using Object Linking and Embedding techniques.